Sensing the Squeeze of Sandwich Generation Women in Jakarta, Indonesia: Sensing the Squeeze of Sandwich Generation Women in Jakarta, Indonesia - Dian Kristiani Irawaty; Maria Gayatri (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The majority of Indonesian women, known as